An Attempt to Relate Oleogel Properties to Wax Ester Chemical Structures - Henriette Brykczynski; Birgit Hetzer; Eckhard Flöter (Gels, 2022)
Wax esters are considered to have a dominant contribution in the gelling properties of wax-based oleogels. To understand their gelling behavior, oleogels of seven different wax esters (total carbon number from 30 to 46; c = 10% [m/m]) in medium-chain triglycerides oil were characterized. Scanning electron microscopy revealed that wax esters crystallize in rhombic platelets with a thickness of 80 to 115 monomolecular layers. Bright field microscopy showed that the regularity and face length of the crystals increased with the total carbon number and molecular symmetry of the respective wax ester. Oscillatory rheology was used to characterize the gel rigidity (<semantics><msubsup>Gmax*</msubsup></semantics>). Here, wax ester oleogels with smaller total carbon numbers yielded higher <semantics><msubsup>Gmax*</msubsup></semantics> values than those of wax esters with higher total carbon numbers. The gel rigidity (<semantics><msubsup>Gmax*</msubsup></semantics>) inversely correlated with the crystal face length. Smaller and optically less well-defined platelets promoted higher gel rigidities. In the case of the microstructure of a specific oleogel composition being manipulated by a variation in the cooling rates (0.8; 5; 10 K/min), this relationship persisted. The information compiled in this manuscript further elucidates the crystallization behavior of wax esters in oleogels. This contributes to the understanding of the composition–structure–functionality relationship of wax-based oleogels supporting future food applications.